Digital Ethics-Based Learning Strategies from an Islamic Education Perspective - Inggi Eka Ria Mentari; Siti Fatimah Sari; Murti Aria Diah Nova; Fahrur Rozy; Aulia Syarah Lubis; Sarah Dina (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study examines digital ethics-based learning strategies from an Islamic Education perspective in response to the growing challenges of technological disruption that have not been matched by the systematic integration of Islamic ethical values into learning. Previous studies have generally treated digital ethics as a normative issue, with limited attention to operational learning strategies grounded in Islamic educational values. This study employs a qualitative library research approach by analyzing primary and secondary sources, including the Qur’an, Hadith, Islamic Education literature, and contemporary studies on digital ethics. Data were analyzed using content analysis and conceptual synthesis to develop an Islamic digital ethics learning framework. The findings indicate that digital ethics-based learning in Islamic Education can be constructed through three interconnected dimensions: (1) the integration of Islamic values, including amanah (trustworthiness), honesty, and adab (etiquette); (2) pedagogical strategies involving digital literacy, ethical communication, and reflective learning; and (3) the evaluation of students’ digital behavior through ethical technology-use indicators. The study contributes a conceptual-operational framework that integrates Islamic values with digital ethics to strengthen students’ digital character in contemporary Islamic education.